Musica Disciplina: a Yearbook of the History of Music. Scribal design in the compilation of Ivrea MS. 115 - Tomasello, Andrew; Carapetyan, Armen (American Institute of Musicology; Hänssler-Verlag, 1988)
The yearbook Musica Disciplina is devoted to the scholarly exploration of early music. In keeping with the title of its first volume (1946), the Journal of Renaissance and Baroque Music, MD seeks to publish in its traditional area of focus studies on Medieval and Renaissance music, but it also invites submissions on music of the seventeenth century. The editor and editorial board encourage submissions of articles on any topic in this broad period. Both traditional and newer approaches are welcomed equally, including, but not limited to, aesthetics and criticism, analytical contributions, archival research, cultural and contextual studies, the history of theory, organology and iconography, performance practices, and source studies. Submissions in English, French, German, Spanish, or Italian are encouraged.